INCREASING STUDENTS’ SCIENCE LEARNING OUTCOMES THROUGHDISCOVERY METHOD IN ONLINE LEARNING AT GRADE VOF SD NEGERI 27 PEKANBARU - Rosmidawati Br Sitinjak (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research was motivated by the low science learning outcomes of grade V students of SD Negeri 27 Pekanbaru. This was seen from 1) the students’ learning outcomes were not optimal, which was proved by the report card scores, especially in science subjects, most of the students did not reach the specified minimum completeness criteria (KKM), 2) students seemed difficult to understand the material presented by the teacher in the classroom and students rarely answered the questions given by the teacher. This study aimed to improve students’ science learning outcomes at grade V of SD Negeri 27 Pekanbaru. The subjects of this study were 30 grade V students of SD Negeri 27 Pekanbaru. This study was classroom action research. The research instrument consisted of learning outcomes instruments and data collection instruments in the form of observation sheets for teacher’s activities and students’ activities. Based on the results of the analysis and discussion, it was concluded that the application of Discovery Learning method in online learning improved the students’ learning outcomes in science lessons at grade V of SD Negeri 27 Pekanbaru. This success was evidenced by an increase in learning outcomes before taking action in cycle I and cycle II. Before taking the action, the students’ learning outcomes were classified as